Plasticity of Adipose Tissue-Derived Stem Cells and Regulation of Angiogenesis - Panina, Yulia A.; Yakimov, Anton S.; Komleva, Yulia K.; Morgun, Andrey V.; Lopatina, Olga L.; Malinovskaya, Natalia A.; Shuvaev, Anton N.; Salmin, Vladimir V.; Taranushenko, Tatiana E.; Salmina, Alla B. (Frontiers in Physiology, 2018)
Adipose tissue is recognized as an important organ with metabolic, regulatory, and plastic roles. Adipose tissue-derived stem cells (ASCs) with self-renewal properties localize in the stromal vascular fraction (SVF) being present in a vascular niche, thereby contributing to local regulation of angiogenesis and vessel remodeling. In last decades, ASCs attract much attention of biologists and bioengineers, particularly, because of their multilineage differentiation potential, strong proliferation and migration abilities in vitro, and high resistance to oxidative stress and senescence. Current data suggest that SVF serves as an important source of endothelial progenitors, endothelial cells, and pericytes, thereby contributing to vessel remodeling and growth. In addition, ASCs demonstrate intriguing metabolic and interlineage plasticity which make them good candidates for creating regenerative therapeutic protocols, in vitro tissue models and microphysiological systems, tissue-on-chip devices for diagnostic and regeneration-supporting purposes. This review covers recent achievements in understanding the metabolic activity within the SVF niches (lactate and NAD+ metabolism) which is critical for maintaining the pool of ASCs, and disclosure of their pro-angiogenic poteintial, particularly, in the complex therapy of cardiovascular and cerebrovascular diseases.